Modulation of caveolae by insulin/IGF‐1 signaling regulates aging of Caenorhabditis elegans. (26th June 2018) - Roitenberg, Noa; Bejerano‐Sagie, Michal; Boocholez, Hana; Moll, Lorna; Marques, Filipa Carvalhal; Golodetzki, Ludmila; Nevo, Yuval; Elami, Tayir; Cohen, Ehud
Abstract: Reducing insulin/IGF‐1 signaling (IIS) extends lifespan, promotes protein homeostasis (proteostasis), and elevates stress resistance of worms, flies, and mammals. How these functions are orchestrated across the organism is only partially understood. Here, we report that in the nematode Caenorhabditis elegans, the IIS positively regulates the expression of caveolin‐1 ( cav‐1 ), a gene which is primarily expressed in neurons of the adult worm and underlies the formation of caveolae, a subtype of lipid microdomains that serve as platforms for signaling complexes. Accordingly, IIS reduction lowers cav‐1 expression and lessens the quantity of neuronal caveolae. Reduced cav‐1 expression extends lifespan and mitigates toxic protein aggregation by modulating the expression of aging‐regulating and signaling‐promoting genes. Our findings define caveolae as aging‐governing signaling centers and underscore the potential for cav‐1 as a novel therapeutic target for the promotion of healthy aging. Synopsis: In the nematode C. elegans, the aging‐regulating, insulin/IGF signaling (IIS) cascade, positively regulates the expression of cav‐1, a gene that encodes the protein caveolin‐1, which induces the formation of a unique subtype of "lipid rafts", known as "caveolae". Accordingly, knocking down IIS activity reduces the expression of cav‐1 and lessens the number of neuronal caveolae. Likewise, the knockdown of cav‐1 extends lifespan and protects the worm from toxic protein aggregation. These results unveil a novel role for lipid assemblies in the regulation of aging. The insulin/IGF signaling (IIS) cascade positively regulates the expression of cav‐1 . IIS reduction lowers the expression of cav‐1 and lessens the number of caveolae, primarily in neurons. Knocking down cav‐1 modulates signaling, extends lifespan and promotes proteostasis. Abstract : In C. elegans, caveolin‐1 expression and the formation of caveolae is positively regulated by the aging‐regulating insulin/IGF (IIS) cascade. The knockdown of cav‐1 extends lifespan and protects the worm from toxic protein aggregation, linking lipid assemblies to the regulation of aging.